PENGUATAN PENDIDIKAN BAGI ARSIPARIS: Array - Sari Hasanah (Jurnal Kearsipan, 2018)
This paper aims to describe problems faced by archivists and efforts to overcome them from educational perspective. This study limits its scope within formal education. The methods used in collecting data are observation and interviews. The problems are quantity and quality of professional archivists. Many institutions do not have professional archivists. Full time archival education is urgently needed. Efforts should be made to improve quality and quantity of the existing archival study programs and the relation between national archival institution and higher education.